IMPLEMENTATION OF CHARACTER EDUCATION LOCAL WISDOM CHARGED IN BASIC EDUCATION LEVEL IN SOUTH SUMATRA - UMI CHOTIMAH (Sriwijaya University Learning and Education International Conference, 2016)
The aims of this study is to analyze the implementation of character education charged local wisdom in Basic Education in South Sumatra province and its obstacle factors. This study used a combination of quantitative and qualitative approach with descriptive methods. The study is conducted in three cities (Palembang, Prabumulih and Lubuk Linggau), and three regencies (MusiBanyuasin, Lahatand OganKomeringIlir), withtotal respondentsare 190 teachers. The data collection by using focus group discussions and questionnaires, while data analysis was done descriptively. The results showed that the implementation of character education local wisdom charged in basic education level in South Sumatra province in general already performing well but is not maximized. The majority (76.84%) of schools have implemented character education charged with quite good local wisdom. In junior high schools have done a good (13.04%) compared with SD (9.92%). In Prabumulih, most schools do it well (16.67%), while most schools do it less well in Lahat (18.42%). The elements of the local wisdom that is used is the poem, folklore, or aphorisms typical South Sumatra, utilization of used goods, the use of distinctive arts areas such as sarofalanam, tambourine, weaving mats and sewed roof, making conblock, literacy Al-Qur'an, and gardening (pineapple, mango, litchi).Not maximal implementation of character education charged local wisdom is influenced by factors: a lack of understanding and commitment of teachers with a lack of training, limitation of infrastructure of the schools, lack of cooperation of parents and the community, and lack of human resources teachers.